Analisis Putusan Sengketa Ekonomi Syariah Pengadilan Pasaman Barat Tentang Putusan Arbitrase Bpsk Nomor 1409/ARB/BPSK-BB/IX/2016 - Suhairi, Mhd Arbi Bayu; Harahap, Mhd. Yadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The great interest of the public today regarding Islamic economics, in line with the increasingly massive number of people who become customers in all Islamic Banks, which is likely to have an impact on the emergence of disputes. As an example at this time is the matter of sharia economic disputes, initially a consumer protection complaint was made through BPSK Batu Bara Regency, which then the BPSK Decision was made a Legal Objection to the West Pasaman District Court with Decision Number 55/Pdt.Sus-BPSK/2016/PN.Psb by Bank Syariah Mandiri Pasaman Barat, and was appealed to the Supreme Court of the Republic of Indonesia with Decision Number 622 K/Pdt.Sus-BPSK/2017. The purpose of this study is to determine the extent to which the law enforcement of dispute resolution is in accordance with the provisions and its application seen from the contents of the decision number Case Number 622 K/Pdt.Sus-BPSK/2017; and Decision Number 55/Pdt.Sus-BPSK/2016/PN Psb. While the location of the Dispute is in West Pasaman, West Sumetara. The result of this research is that it turns out that there is still a limited understanding of the actors of Islamic banking business activities who do not fully understand the regulations.